Anti-aging nitrile rubber sealing material as well as preparation method and application thereof

By using small-size and highly compatible graphene quantum dots in rubber sealing materials, the problem of aging of traditional materials in high temperature and high pressure environments is solved, which significantly improves sealing and aging resistance and extends service life.

CN119842122APending Publication Date: 2025-04-18CHINA NAT PETROLEUM CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311341384.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing rubber sealing materials age under high temperature, high pressure, high stress and harmful gas environments, resulting in reduced sealing properties and shortened service life. In addition, traditional antioxidants and fillers have poor compatibility when improving aging resistance, affecting the crosslinking network, making it difficult to effectively improve sealing properties.

Method used

Graphene quantum dots with extremely small size (≤100nm) and good compatibility with rubber are used as additives. Through its two-dimensional structure and rich functional groups, free radicals are captured, mechanical properties are enhanced, phase interfaces are improved, and the formation of cross-linking networks is promoted, thereby improving the aging resistance and sealing of rubber.

Benefits of technology

The aging resistance and sealing properties of nitrile rubber sealing materials have been significantly improved. After 14 days of aging in high-temperature diesel media, the strength drops by less than 10%, extends the service life, and maintains excellent comprehensive performance during the vulcanization process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004497371860000061
    Figure BDA0004497371860000061
  • Figure BDA0004497371860000071
    Figure BDA0004497371860000071
  • Figure BDA0004497371860000072
    Figure BDA0004497371860000072
Patent Text Reader

Abstract

The invention belongs to the technical field of rubber sealing materials, and particularly relates to an anti-aging nitrile rubber sealing material as well as a preparation method and application thereof. The anti-aging nitrile rubber sealing material is prepared from the following raw materials in parts by weight: 20-80 parts of nitrile rubber; 1-10 parts of zinc oxide; 3 to 10 parts of zinc stearate; 5 to 12 parts of triallyl isocyanurate; 5 to 30 parts of graphene quantum dots; and 5 to 10 parts of dicumyl peroxide. The graphene quantum dots which are extremely small in size (smaller than or equal to 100 nm) and good in compatibility with rubber are adopted as the additive, and the problems that a traditional carbon material is poor in compatibility with the rubber and vulcanization crosslinking of the traditional carbon material is physically blocked are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber sealing materials, and in particular relates to an aging-resistant nitrile rubber sealing material and a preparation method and application thereof. Background Art

[0002] During the oil and gas development process, non-metallic sealing materials used in drilling and production equipment face harsh working conditions such as high temperature, high pressure, high stress, high carbon dioxide, and hydrogen sulfide. The sealing and aging problems of rubber sealing materials used in packers and wellhead equipment are hot topics in the research field of materials. The development of rubber sealing materials with excellent aging resistance has become one of the most critical technologies in modern oil production engineering technology.

[0003] Overcoming rubber sealing and aging is a key technical problem that has not been well solved in the industry for a long time. Existing literature has reported that adding small molecule antioxidants such as metal oxides and phenolic compounds to the rubber matrix can improve the aging resistance of rubber to a certain extent. However, these additives not only show poor compatibility with the rubber matrix, but are also easily precipitated from the rubber matrix, making it difficult to effectively improve its sealing and aging resistance. Moreover, too much filler will greatly affect the formation of the rubber cross-linking network, thereby greatly affecting its sealing. Therefore, the high-temperature thermal oxidation aging problem of rubber materials has not been well solved. In recent years, carbon materials with electron cloud sp2 hybrid structure have become a research hotspot. Their stable conjugated electron cloud structure can efficiently capture free radicals containing unpaired electrons. Multi-walled carbon nanotubes can effectively improve the thermal oxidation aging behavior of fluorosilicone rubber after being compounded with fluorosilicone rubber. The two-dimensional planar honeycomb crystal structure of graphene sp2 hybridization has also been found to have the ability to capture free radicals in the composite modification study of hydrogenated nitrile rubber (HNBR). However, the easy aggregation of carbon materials such as carbon nanotubes and graphene prevents them from being widely used in composite applications of high-performance rubber.

[0004] The Chinese patent application number 201910799343.1 discloses a cold-resistant and aging-resistant nitrile rubber sealing material and a preparation method thereof, which is composed of the following raw materials: nitrile rubber, chloroprene rubber, K2Ti6O 13 Whiskers, zinc oxide, ethylene-octene copolymer grafted maleic anhydride, nano diatomite, nano zinc oxide, carbon black, silane coupling agent, stearic acid, antioxidant, antioxidant, vulcanizing agent, accelerator. The nitrile rubber sealing material prepared by the invention has good aging resistance and cold resistance, but the improvement of the aging resistance of the invention is mainly through K2Ti6O 13 It is obtained by using whiskers and traditional antioxidants and anti-aging agents, which mainly targets the thermal aging performance of rubber in air, and no research has been done on the improvement of the aging performance of rubber in diesel medium.

[0005] In addition, patent CN113388176A discloses a high-performance nitrile rubber material and a preparation method thereof, although it adopts carbon quantum, on the one hand, its carbon quantum is prepared by using silane coupling agent and citric acid as raw materials. In addition, it mixes carbon quantum into raw materials to solve the problem that nitrile rubber material is difficult to take into account oil resistance and low temperature resistance at the same time. The mechanism of action of its carbon quantum is: as a solubilizing agent, it plays a role in strengthening and improving the bonding effect of the phase interface in a number of systems, and its surface functional groups can promote the formation of a cross-linked network in the rubber at the same time.

[0006] The graphene quantum dots used in the present invention have many differences in structure and properties from carbon quantum dots:

[0007] Structure: Graphene quantum dots are nanomaterials separated from graphene sheets, with a two-dimensional structure similar to graphene and a thickness of about several nanometers; while carbon quantum dots are spherical nanoparticles formed by the aggregation of carbon atoms, with a diameter generally ranging from a few nanometers to tens of nanometers;

[0008] Optical properties: Graphene quantum dots have a wide band gap and high light absorption capacity, can absorb and emit light in the visible and near-infrared ranges, and have excellent photoelectric conversion performance; while carbon quantum dots have a wide band gap and fluorescence emission characteristics due to their smaller size and quantum confinement effect, and are widely used in fields such as bioimaging and optoelectronic devices;

[0009] Surface functional groups: Graphene quantum dots usually have abundant functional groups on their surface, such as hydroxyl, carboxyl, amino, etc., which make them have good solubility and biocompatibility, and are suitable for applications such as biomedicine and drug delivery. However, carbon quantum dots have relatively few surface functional groups, and usually need to be chemically modified to improve their solubility and functionality.

[0010] Electronic structure: Graphene quantum dots have the special electronic structure of graphene, with high carrier mobility and good electron transmission performance, and are suitable for electronic devices and energy storage. Carbon quantum dots, due to their smaller size and quantum confinement effect, have the potential for bandgap width regulation and energy level regulation, and are suitable for optoelectronic devices and catalysts.

[0011] Many differences determine that the carbon quantum in the prior art and the graphene quantum used in the present invention have different applications and effects. Summary of the invention

[0012] In order to solve the deficiencies of the prior art, the present invention provides an aging-resistant nitrile rubber sealing material and a preparation method and application thereof. The present invention adopts graphene quantum dots with extremely small size (≤100nm) and good compatibility with rubber as additives, effectively solving the problem that traditional carbon materials have poor compatibility with rubber and physically block their vulcanization crosslinking.

[0013] The technical solution provided by the present invention is as follows:

[0014] An aging-resistant nitrile rubber sealing material is prepared from the following raw materials in parts by weight: 20 to 80 parts of nitrile rubber; 1 to 10 parts of zinc oxide; 3 to 10 parts of zinc stearate; 5 to 12 parts of triallyl isocyanurate; 5 to 30 parts of graphene quantum dots; and 5 to 10 parts of dicumyl peroxide.

[0015] In the above technical solution, graphene quantum dots can be derived from existing technology, preferably, XF215 product 7440-44-0 can be purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., the particle size of which is less than 10nm and evenly distributed, and its powder and solution can emit bright red fluorescence under ultraviolet light. Its surface contains hydroxyl, amino and carboxyl groups.

[0016] In the above technical solution, the added graphene quantum dots have a two-dimensional planar honeycomb crystal structure similar to graphene's sp2 hybridization, which can capture free radicals during the rubber aging process, thereby significantly improving the aging resistance of the rubber; secondly, the extremely small size of the graphene quantum dots themselves makes them disorderly and evenly distributed in the rubber system without affecting the vulcanization of the rubber, thereby having excellent improvement on its physical and mechanical properties and sealing; furthermore, the large number of dangling bonds on the surface of the graphene quantum dots make them have good compatibility in the rubber system, so that they will not aggregate or disperse unevenly during the processing process, thus ensuring the sealing of the rubber sealing material. Finally, after adding graphene quantum dots to the nitrile rubber system, the strength drop is less than 10% after aging in a diesel medium at 100°C for 14 days, which greatly improves its service life compared to traditional nitrile rubber.

[0017] In the present invention, the effects of graphene quantum dots are mainly reflected in the following aspects:

[0018] The first is the solubilization effect. The rich organic functional groups in its surface structure can play a solubilization role and improve the interface of the multiphase system. Compared with the carbon quantum dots disclosed in CN113388176A, the graphene quantum dots used in the present invention have rich functional groups in their structure, while carbon quantum dots generally need to be surface modified to have them;

[0019] The second is the enhancement effect. Graphene quantum dots not only have a two-dimensional structure similar to graphene, which can significantly enhance the mechanical properties of the system, but also the active functional groups on their surface can react with the rubber system to play an inorganic cross-linking role, making the nitrile rubber have good wear resistance.

[0020] Furthermore, the graphene quantum dot structure has better stability (mechanical and thermodynamic) than carbon quantum dots, so introducing it as a filler into nitrile rubber can greatly improve the aging resistance and mechanical aging resistance of its sealing material;

[0021] At the same time, compared with carbon quantum dots, graphene quantum dots retain the two-dimensional structure of graphene. Their smaller size enables them to provide rich physical shielding without hindering the cross-linking of the rubber system itself, thereby significantly improving its sealing properties.

[0022] Finally, the graphene quantum dots preferably used in the present invention can emit bright red fluorescence, and thus have a good indication function, and can be used to quickly identify the uniformity of material processing, and can indicate material loss or aging and shedding when the sealing material is used.

[0023] Specifically, the nitrile rubber is one or a combination of nitrile rubber N230S, nitrile rubber N220S or nitrile rubber N240S.

[0024] Specifically, it is made of the following raw materials in parts by weight: 50 parts of nitrile rubber; 5 parts of zinc oxide; 3 parts of zinc stearate; 5 parts of triallyl isocyanurate; 30 parts of graphene quantum dots; and 7 parts of dicumyl peroxide.

[0025] Specifically, it is made of the following raw materials in parts by weight: 60 parts of nitrile rubber; 2 parts of zinc oxide; 3 parts of zinc stearate; 5 parts of triallyl isocyanurate; 20 parts of graphene quantum dots; and 10 parts of dicumyl peroxide.

[0026] The present invention also provides a preparation method of an aging-resistant nitrile rubber sealing material, comprising the following steps: first, drying 20 to 80 parts of nitrile rubber, then placing it on an open mill for roller plasticization, then sequentially adding 1 to 10 parts of zinc oxide, 3 to 10 parts of zinc stearate, 5 to 12 parts of a cross-linking agent triallyl isocyanurate and 5 to 30 parts of graphene quantum dots, after roller refining, adding 5 to 10 parts of a vulcanizing agent diisopropylbenzene peroxide, until the roller-refined rubber is evenly sheeted, then parking for treatment, and finally using a flat vulcanizer and an electric heating blow box for one-stage vulcanization treatment and two-stage vulcanization treatment respectively, so as to obtain the aging-resistant nitrile rubber sealing material.

[0027] Specifically, the conditions for one-stage vulcanization are: vulcanization temperature of 160-180° C., pressure of 10-20 MPa, and vulcanization time of 1-3 hours.

[0028] Specifically, the conditions of the second stage vulcanization are: vulcanization conditions 140-155° C., pressure 10-20 MPa, and vulcanization 4-8 hours.

[0029] Generally, an increase in the vulcanization temperature will accelerate the vulcanization rate, shorten the scorch time, and reduce the physical properties of the vulcanized rubber. However, the present invention significantly improves the temperature resistance of the system after using graphene quantum dots, and no scorch occurs during long-term vulcanization. The vulcanized rubber has excellent comprehensive properties and does not have the problem of material hardening and volume reduction. It can be seen that the addition of graphene quantum dots has no adverse effect on vulcanization and can ensure that it has excellent aging resistance at high temperatures as a sealing material.

[0030] Specifically, the drying temperature of the nitrile rubber is 60-80°C.

[0031] Specifically, the drying time of the nitrile rubber is 0.5 to 4 hours.

[0032] Specifically, the roller speed ratio of the roll plasticating is 1:(1.20-1.30), preferably, 1:1.25;

[0033] Specifically, the parking treatment time is 20 to 28 hours, preferably 24 hours.

[0034] The invention also provides application of the aging-resistant nitrile rubber sealing material as a rubber sealing material for a packer or wellhead equipment.

[0035] The aging-resistant nitrile rubber sealing material provided by the present invention has excellent aging-resistant performance in terms of tensile strength and sealing performance, and is particularly suitable as a rubber sealing material for packers or wellhead equipment. DETAILED DESCRIPTION

[0036] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0037] Embodiment 1:

[0038] An aging-resistant nitrile rubber sealing material is made from the following raw materials in parts by weight:

[0039]

[0040] The preparation method of the above-mentioned aging-resistant nitrile rubber sealing material comprises the following steps:

[0041] First, the nitrile rubber is dried at a certain temperature (80°C) for a period of time (4h), and then placed on an open mill for uniform roller plasticization (roller speed ratio 1:1.25), and then 5 parts of zinc oxide, 3 parts of zinc stearate, 5 parts of cross-linking agent triallyl isocyanurate and 30 parts of graphene quantum dots are added in sequence. After roller refining for a period of time, 7 parts of vulcanizing agent diisopropylbenzene peroxide are added until the roller refining rubber is uniformly sheeted and parked for 24h. Finally, a flat plate vulcanizer and an electric heating blower are used for a first-stage vulcanization treatment, respectively, with the vulcanization conditions of temperature 180°C, pressure 10MPa, and vulcanization time 3h; a second-stage vulcanization treatment, with the vulcanization conditions of 155°C and vulcanization for 4h, to obtain a nitrile rubber material with excellent sealing performance and aging resistance.

[0042] Embodiment 2:

[0043] An aging-resistant nitrile rubber sealing material is made from the following raw materials in parts by weight:

[0044]

[0045] The preparation method of the above-mentioned aging-resistant nitrile rubber sealing material comprises the following steps:

[0046] First, the nitrile rubber is dried at a certain temperature (70°C) for a period of time (4h), and then placed on an open mill for uniform roller plasticization (roller speed ratio 1:1.25), and then 2 parts of zinc oxide, 3 parts of zinc stearate, 5 parts of cross-linking agent triallyl isocyanurate and 20 parts of graphene quantum dots are added in sequence. After roller refining for a period of time, 10 parts of vulcanizing agent diisopropylbenzene peroxide are added until the roller refining rubber is uniformly sheeted, and then parked for 24h. Finally, a flat vulcanizer and an electric heating blower are used for a first-stage vulcanization treatment, respectively, with the vulcanization conditions of temperature 160°C, pressure 20MPa, and vulcanization time 2h; a second-stage vulcanization treatment, with the vulcanization conditions of 145°C and vulcanization time 8h, to obtain a nitrile rubber material with excellent sealing performance and aging resistance.

[0047] Embodiment 3:

[0048] An aging-resistant nitrile rubber sealing material is made from the following raw materials in parts by weight:

[0049]

[0050]

[0051] The preparation method of the above-mentioned aging-resistant nitrile rubber sealing material comprises the following steps:

[0052] First, the nitrile rubber is dried at a certain temperature (75°C) for a period of time (4h), and then placed on an open mill for uniform roller plasticization (roller speed ratio 1:1.25), and then 7 parts of zinc oxide, 5 parts of zinc stearate, 6 parts of cross-linking agent triallyl isocyanurate and 25 parts of graphene quantum dots are added in sequence. After roller refining for a period of time, 4 parts of vulcanizing agent diisopropylbenzene peroxide are added until the roller refining rubber is uniformly sheeted and parked for 24h. Finally, a flat plate vulcanizer and an electric heating blower are used for a first-stage vulcanization treatment, respectively, and the vulcanization conditions are: temperature 180°C, pressure 10MPa, and vulcanization time 3h; a second-stage vulcanization treatment, the vulcanization conditions are 155°C, pressure 15MPa, and vulcanization 4h, and a nitrile rubber material with excellent sealing performance and aging resistance can be obtained.

[0053] Comparative Example 1:

[0054] A nitrile rubber sealing material, which is different from Example 1 in that the raw materials do not contain graphene quantum dots, and other raw materials and preparation methods are the same as Example 1.

[0055] Comparative Example 2:

[0056] A nitrile rubber sealing material, which is different from Example 1 in that the graphene quantum dots in the raw materials are replaced by carbon quantum dots (purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., code-named XF253), and other raw materials and preparation methods are the same as Example 1.

[0057] Performance Test:

[0058] The aging performance of the nitrile rubber material in Example 1-2 in diesel medium was tested according to GB / T 1690-2010, with a test temperature of 100° C. and a test time of 14 days (336 h).

[0059] Table 1 Performance test results

[0060]

[0061] As shown in Table 1, the nitrile rubber sealing materials prepared in Examples 1-3 of the present invention have excellent aging resistance in diesel medium. After aging treatment in 100°C diesel medium for 14 days, the tensile strength of the nitrile rubber sealing materials prepared in Examples 1-3 does not change much (decline < 10%). The tensile strength of the nitrile rubber sealing material without adding graphene quantum dots in Comparative Example 1 is lower than that of the nitrile rubber with added graphene quantum dots, and after aging treatment in 100°C diesel medium for 14 days, its tensile strength decreases significantly (decline > 20%). The tensile strength of the nitrile rubber sealing material with carbon quantum dots added in Comparative Example 2 is lower than that of the nitrile rubber with added graphene quantum dots, and after aging treatment in 100°C diesel medium for 14 days, its tensile strength decreases significantly (decline of 19.4%). It can be seen that the addition of graphene quantum dots can effectively improve the tensile properties and diesel medium aging resistance of nitrile rubber.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An aging-resistant nitrile rubber sealing material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 20 to 80 parts of nitrile rubber; 1 to 10 parts of zinc oxide; 3 to 10 parts of zinc stearate; 5 to 12 parts of triallyl isocyanurate; 5 to 30 parts of graphene quantum dots; and 5 to 10 parts of diisopropylbenzene peroxide.

2. The aging-resistant nitrile rubber sealing material according to claim 1, characterized in that: The nitrile rubber is one of nitrile rubber N230S, nitrile rubber N220S or nitrile rubber N240S, or a combination of several of them.

3. The aging-resistant nitrile rubber sealing material according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 50 parts of nitrile rubber; 5 parts of zinc oxide; 3 parts of zinc stearate; 5 parts of triallyl isocyanurate; 30 parts of graphene quantum dots; and 7 parts of dicumyl peroxide.

4. The aging-resistant nitrile rubber sealing material according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 60 parts of nitrile rubber; 2 parts of zinc oxide; 3 parts of zinc stearate; 5 parts of triallyl isocyanurate; 20 parts of graphene quantum dots; and 10 parts of dicumyl peroxide.

5. A method for preparing an aging-resistant nitrile rubber sealing material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: first, drying 20 to 80 parts of nitrile rubber, and then placing the nitrile rubber on an open mill for uniform roller plasticization, and then sequentially adding 1 to 10 parts of zinc oxide, 3 to 10 parts of zinc stearate, 5 to 12 parts of triallyl isocyanurate as a cross-linking agent and 5 to 30 parts of graphene quantum dots, and after roller refining, adding 5 to 10 parts of diisopropylbenzene peroxide as a vulcanizing agent, until the roller-refined rubber is uniformly sheeted, and then parking for treatment, and finally using a flat vulcanizer and an electric heating blow box for one-stage vulcanization treatment and two-stage vulcanization treatment respectively, so as to obtain the aging-resistant nitrile rubber sealing material.

6. The method for preparing the aging-resistant nitrile rubber sealing material according to claim 5, characterized in that: The conditions for one-stage vulcanization are: vulcanization temperature 160-180°C, pressure 10-20MPa, and vulcanization 1-3h.

7. The method for preparing the aging-resistant nitrile rubber sealing material according to claim 5, characterized in that: The conditions of the second stage vulcanization are: vulcanization conditions 140 ~ 155 ° C, pressure 10 ~ 20MPa, vulcanization 4 ~ 8h.

8. The method for preparing the aging-resistant nitrile rubber sealing material according to claim 5, characterized in that: Meet any one or more of the following conditions: The drying temperature of nitrile rubber is 60-80°C; The drying time of nitrile rubber is 0.5 to 4 hours; The roller speed ratio of the roller plasticating is 1:(1.20~1.30); The parking processing time is 20 to 28 hours.

9. An application of the aging-resistant nitrile rubber sealing material according to any one of claims 1 to 4, characterized in that: As rubber sealing material for packers or wellhead equipment.

Citation Information

Patent Citations

  • Cold-resistant aging-resistant nitrile rubber sealing material and preparation method thereof

    CN110372926A

  • High-performance nitrile rubber material and preparation method thereof

    CN113388176A

  • Graphene quantum dot / rubber nano composite material

    CN107501646A

  • Graphene reinforced rubber sealing material and preparation method thereof

    CN110183749A

  • Graphene quantum dot reinforced fiber as well as preparation method and application thereof

    CN113430663A